Prevailing Perceptions and the Growth of Private Label Brands in Africa and Europe: An Overview - Sbonelo Ndlovu (Journal of Economics and Behavioral Studies, 2019)
This paper reviewed the existing literature in different parts of the continents, focusing specifically in Africa and Europe, critically reviewing past and recent literature of studies on customers’ perceptions towards private label brands. Such review article enabled the writer to understand the prevailing state of private label brands across different continents; in the process enabling grocery retailers, marketing practitioners and academics a clear view of the state of customers’ perceptions around the globe. The results found that the international state of private label brands has somehow improved in some parts of the globe, especially in Europe and Americas, where private label brands have enormously improved customers perceptions of their private label brands and in the process actively competing with national brands for the market share. Opposing such success, In Africa there seems to be somehow lack of improvement in the early perceptions of private label brands in the process not fully challenging national brands. Noticeably, in Africa there seems customers still perceive private label brands as alternatives of national brands in tough economic conditions. Hence, grocery retailers need to extensively invest on their private label brands in order to competitively challenge and change existing customer perceptions. Key investments should be in branding, promoting and educating customers about private label brands.